Transitional Justice in Indonesia: The Persistent Challenge of Addressing the 1965-1966 Mass Killings - Mkumbi, Dyamwale Amir; Soetjipto, Ani Widyani (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2025)
This article explores why Indonesia has struggled to achieve meaningful transitional justice for the 1965-1966 mass killings despite ongoing democratic reforms and advocacy efforts. These events, which led to the deaths of an estimated 500,000 to one million alleged communists, remain unaddressed due to entrenched political and military power, societal resistance, and ineffective judicial mechanisms. Using a qualitative approach, this research examines survivor testimonies, official reports from institutions such as Komnas HAM, and scholarly literature to understand the underlying challenges. The findings suggest that Indonesia's inability to confront these past atrocities stems from a lack of political will, continued military influence, and a deeply ingrained culture of silence reinforced by decades of state propaganda. While international advocacy efforts, including the International People's Tribunal (IPT) and grassroots movements, have shed light on the issue, systemic obstacles impede progress. This study highlights the potential benefits of hybrid courts, an independent truth commission, and comprehensive reparations programs by comparing Indonesia's situation with transitional justice efforts in South Africa and Cambodia. These reforms are crucial for addressing historical injustices, fostering national reconciliation, and promoting long-term accountability. Keywords: Transitional justice, 1965-1966 killings, Indonesia, Human rights, Impunity Artikel ini membahas mengapa Indonesia kesulitan untuk mencapai keadilan transisional yang bermakna untuk pembunuhan massal tahun 1965-1966, meskipun telah melakukan reformasi demokrasi dan upaya advokasi yang berkelanjutan. Peristiwa yang mengakibatkan kematian sekitar 500.000 hingga satu juta orang yang dituduh komunis ini, masih belum terselesaikan karena kuatnya kekuasaan politik dan militer, resistensi masyarakat, dan mekanisme peradilan yang tidak efektif. Dengan pendekatan kualitatif, penelitian ini menganalisis kesaksian korban, laporan para penyintas, laporan resmi dari institusi Komnas HAM, dan literatur akademis untuk memahami tantangan mendasar yang ada. Temuan penelitian menunjukkan bahwa ketidakmampuan Indonesia dalam menghadapi kekejaman masa lalu ini disebabkan oleh kurangnya kemauan politik, pengaruh militer yang masih kuat, serta budaya “diam” yang mengakar akibat propaganda negara selama puluhan tahun. Meskipun upaya advokasi internasional, seperti International People's Tribunal (IPT), dan gerakan akar rumput telah menyoroti masalah ini, hambatan sistemis menghalangi kemajuan. Studi ini menekankan potensi manfaat dari pengadilan hibrida, komisi kebenaran yang independen, dan program reparasi komprehensif dengan membandingkan situasi Indonesia dengan upaya keadilan transisional di Afrika Selatan dan Kamboja. Reformasi ini penting untuk mengatasi ketidakadilan sejarah, memupuk rekonsiliasi nasional, dan mendorong akuntabilitas jangka panjang. Kata-Kata Kunci: Keadilan transisional, Pembunuhan 1965-1966, Indonesia, Hak asasi manusia, Impunitas